Observing accelerated chemical colour change in aspen and birch wood using hyperspectral imaging and spectrophotometry - Lampela, Joona; Keinänen, Markku; Haapala, Antti; Akinyemi, Olusegun; Möttönen, Veikko (Springer Nature, 2025)
Natural weathering gradually turns wood light grey over years, driven by exposure to sunlight, precipitation, and biological agents. Nontoxic chemicals have been used to accelerate artificial weathering-induced colour changes in wood. This study aimed to evaluate the effectiveness and underlying mechanisms of various surface treatment chemicals and a commercial silicon-based product in accelerating UV-induced colour changes in birch and aspen under artificial weathering conditions. Weathering was conducted by using an artificial weathering testing instrument with or without spraying the samples with water. Colour changes were measured with a portable spectrophotometer. Hyperspectral imaging data were included to visualise spatial variations of colour in wood samples. The use of water was a significant factor in determining the colour change in wood. Mostly photodegraded lignin constituents leached out of the wood with water spraying but remained if it was not used. The treatment chemicals caused distinct colour changes: Iron (II) sulphate caused dark grey staining, citric acid a unique red colour, sodium hydroxide darkening and brown hue, and hydrogen peroxide the most uniform colour. Commercial silicon-based product caused either little or no noticeable colour change over control samples. The greatest potential for colour change occurred during the first hours of artificial weathering. Spatial data of hyperspectral images allowed for more accurate estimation of variability over spectrophotometer data, and use of hyperspectral imaging in further research is therefore suggested.
Keywords: artificial weathering; wood colour change; surface treatment chemicals; hyperspectral imaging; lignin photodegradation